A comparative study of mechanical, thermal and electrical properties of graphene-, graphene oxide- and reduced graphene oxide-doped microfibrillated cellulose nanocomposites. (15th August 2018) - Phiri, Josphat; Johansson, Leena-Sisko; Gane, Patrick; Maloney, Thad
Abstract: Micro-nanofibrillated cellulose (MFC/NFC) and graphene-based composites are interesting materials due to their complementary functional properties, opening up potential in a variety of applications. Graphene, graphene oxide (GO) and reduced graphene oxide (RGO) were used in this comparative study as reinforcement functional fillers for the fabrication of multifunctional MFC nanocomposites using a simple aqueous dispersion based mixing method. The MFC composites showed different properties depending on the type of filler used. Graphene was seen to agglomerate and was poorly dispersed in the MFC matrix, whilst GO and RGO were homogeneously dispersed due to the presence of functional groups that promoted a strong interfacial molecular interaction between the filler and the MFC matrix. At 0.6 wt% filler loading, the tensile strength for MFC/GO and MFC/RGO increased by 17 % and 22 %, respectively, whilst the Young's modulus increased from 18 GPa to 21 GPa and 25 GPa, respectively. Compared to the neat MFC, addition of 5 wt% of graphene enhanced the thermal stability by 5 % and whilst with the addition of GO and RGO stability increased by 2 and 3 %, respectively. Graphene/MFC and RGO/MFC showed a high electrical conductivity of 1.7 S m -1 and 0.5 S m -1, respectively while the GO reinforced composites were insulators.